Determination and Prioritizing of Addiction Prevention Factors in Delfan City, Iran - Davod Mirzaei; Bibi Eshrat Zamani; Sayyed Hojat Mousavi (Addiction and Health, 2011)
Background: In recent decades, drug abuse has been one of the most important problems of human societies and has been imposing enormous charges to them. Exposing addicts to infectious diseases, social and economic harmful impacts, expensive and reversibility of treatment methods have caused that drug abuse prevention programs be more inexpensive and more effective than treatment. One of the most important methods of drug abuse prevention is identification and prioritization of them according to scientific methods. The purpose of this study was to investigate addiction prevention methods among adolescents and teenagers from the viewpoints of addicts, their parents, authorities and prioritizing the prevention methods based on analytical hierarchy process (AHP) model in Delfan city.Methods: Statistical samples included 17 authorities, 42 addicts, and 23 parents that have been selected through purposive sampling. Data collection instruments involved structured and semi-structured interviews. Data were analyzed based on quantitative and qualitative methods, encoding and categorization. In this study, AHP model was used for prioritizing the prevention methods. This model is one of the most efficient and comprehensive designed techniques for multi-criteria decision making; it formulates the possibility of natural complex problems as hierarchy.Findings: The results indicated that the most important methods of drug abuse prevention were using media, case studies, planning for leisure times, educating social skills, integrating drug prevention methods in religious customs and respect to teenagers. Among these factors, the media and respect to adolescents with weights 0.3321 and 0.2389 had the highest preferences for the prevention of drug addiction, respectively. Planning for leisure time with weight of 0.1349 had the lowest importance than media and teenager respectful factor and higher priority than religion customs, dating and learning lessons factors. On the contrary, integrating in religion customs, using case studies with weights 0.1145, 0.1114 and 0.0680 had the lowest preferences, respectively, and can be considered in later settings.Conclusion: The interviewees mentioned the most important addiction prevention methods in respect to teenagers, religious customs, media, dating skills, learning lessons from examples and attention to the leisure times among which the media has been the most efficient method. Because, publicity of the media as a national media is available to the public and it is not dedicated for a special group or class of people and everyone can use it regardless of his literacy and knowledge level.Keywords: Addiction, Analytical hierarchy process model, Prioritizing, Prevention methods.